DEVELOPMENT OF LEARNING TOOLS USING THE ECIRR MODEL ON COLLOID MATERIAL TO IMPROVE SCIENCE PROCESS SKILLS - Hayatunnufus, Gina; Supardi, Supardi (PT. Antis International Publisher, 2025)
Objective: This study aims to develop learning tools based on the ECIRR (Elicit, Confront, Interpret, Resolve, Reinforce) model for colloidal material to enhance students' science process skills. Method: The research employed the ADDIE development model, encompassing Analyze, Design, Development, Implementation, and Evaluation phases. Learning tools were validated by experts using Aiken’s V formula, and a limited implementation was carried out among grade XI MIPA students. Results: The validation results yielded an average Aiken’s V count of 0.87, indicating high validity. Furthermore, student responses to the developed learning tools showed a positive perception, with an average response rate of 90%, categorized as very good. Novelty: The integration of the ECIRR learning model into science learning tools presents a novel approach that shifts from traditional methods to a student-centered learning paradigm. This development addresses the gap between curriculum expectations and classroom practices by fostering active learning and improving students’ engagement and process skills in understanding colloidal concepts.